Laparoscopic mucosectomy for gastric duplication cysts that communicated with the spleen in a 10‐year‐old girl: A case report. Issue 3 (12th November 2020) - Kohara, Yuichiro; Zuo, Shogo; Sawai, Toshio; Kanehiro, Hiromichi; Sho, Masayuki
Abstract: We report a case of laparoscopic mucosectomy for gastric duplication cysts that communicated with the spleen. A 10‐year‐old girl visited a local hospital with a chief complaint of intermittent left abdominal pain that had lasted for about 2 months. We diagnosed two gastric duplication cysts by ultrasonography and planned a laparoscopic extirpation. The elliptical masses were found in the splenic hilum and were 5 and 3 cm in diameter. The bigger one communicated with the spleen, so cystectomy could not be performed. Considering the risk of hemorrhage and the patient's age, we performed a mucosectomy rather than a partial splenectomy. The patient had an uneventful postoperative course. We histologically diagnosed gastric duplication cysts. Laparoscopic mucosectomy is a useful procedure for gastric duplication cysts that communicate with the spleen.